[1R-(1 alpha,2 alpha,4 alpha,5 beta,6 alpha,7 alpha)]-4-Benzoyloxymethyl-5,6-dihydroxy-3,8-dioxatricyclo[5.1.0.0(2,4 )]octan-5-yl acetate (3-deacetylcrotepoxide) from Kaempferia rotunda Val - Sirat, H.M.; Feng, Y.S.; Awang, K.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C16H16O7, isolated from Kaempferia rotunda rhizomes, features a six-membered cyclohexane ring that adopts a twisted-boat conformation owing to the presence of two adjacent epoxide attachments that lock in four of the six axial positions. The CH3CO2- and HO- substituents occupy equatorial positions. However, the bond angles at the ring carbon connected to the C6H5CO2CH2- substituent deviate signifcantly from the idealized tetrahedral angles as the carbon atom is part of an epoxide ring. In the crystal, the molecules are linked into chains by O-H center dot center dot center dot O hydrogen bonds.